Genome-wide association mapping of loci conferring all-stage and high-temperature adult-plant resistance to stripe rust in a global spring barley collection - Arjun Upadhaya; Meinan Wang; Nosheen Fatima; Matthew Brooke; Travis Ruff; Deven R. See; Robert Brueggeman; Xianming Chen (Theoretical and Applied Genetics, 2025)

Genotyping by Multiplexed Sequencing (GMS) protocol in Barley - Jonathan Eagle; Travis Ruff; Marcus Hooker; Sajal Sthapit; Elliott Marston; Karol Marlowe; Dolores Covarrubias; Daniel Skinner; Patrick Hayes; Jamie Sherman; Deven See (Euphytica, 2021)
Genotyping by sequencing (GBS) and single nucleotide polymorphism (SNP) chip technologies are the primary SNP genotyping technologies used today. However, these genotyping technologies have some drawbacks that limit their usefulness in analysis. We have developed a robust protocol called genotyping by multiplexed sequencing (GMS) using SNP markers, providing informative genotypic data with greater flexibility. The genotypes derived from direct sequence reads reduce ambiguity in genetic analysis. The advantages of this protocol include: (1) This PCR-based direct sequencing protocol generates information from markers of interest and provides a more streamlined and accurate analysis process, by multiplexing hundreds of informative markers into a single sequencing run. (2) The marker sets are easily customized to the species of interest and can readily be changed. In this study we have taken the GMS protocol developed in wheat and adapted it to barley. We have identified 577 SNP markers that work well using this protocol providing adequate genome coverage for genomic selection and tag 267 QTL’s for genes of interest. Good markers have an adequate read depth of at least 5 amplicons and are reliably present across the population.